Effectiveness of oral glutathione in reducing nitric oxide and IL-1? concentrations for clinical improvement in mild to moderate acne vulgaris: - Mawu, Ferra Olivia (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Acne vulgaris (AV) is a chronic inflammatory dermatosis predominantly affecting adolescents and young adults. Oxidative and nitrosative stress, marked by elevated nitric oxide (NO) and interleukin (IL)-1?, contributes to AV pathogenesis. Glutathione, a key antioxidant, may attenuate oxidative and nitrosative stress and modulate inflammatory pathways. This study investigates the effectiveness of oral glutathione supplementation on serum NO and IL-1? concentrations, and clinical improvement in mild to moderate AV patients. Methods: A randomized controlled trial was conducted involving 40 subjects diagnosed with mild to moderate AV. Participants were randomized to receive either 500 mg oral glutathione (n = 22) or placebo (n = 18) once daily for 4 weeks. Clinical severity of AV was assessed utilizing the Lehmann criteria. Serum levels of NO and IL-1? were measured at baseline and week 4. Results: At week 4, reductions in serum NO and IL-1? concentrations were observed in the glutathione group; however, these changes did not reach statistical significance (p > 0.05). Clinical improvement occurred in seven subjects (31.8%) in the glutathione group, with a reduction from moderate to mild severity. No adverse reactions were reported. Conclusions: Oral glutathione supplementation demonstrated a non-significant trend toward reducing oxidative and nitrosative stress markers and improving mild to moderate AV. Further studies are recommended to validate these findings.
Keywords: acne vulgaris; akne vulgaris; dušikov oksid; glutathione; glutation; interleukin-1?; interlevkin-1?; nitric oxide; oksidativni stres; oxidative stress